Oral phytate supplementation on the progression of mild cognitive impairment, brain iron deposition and diabetic retinopathy in patients with type 2 diabetes: a concept paper for a randomized double blind placebo controlled trial (the PHYND trial) - Pujol, Antelm; Sanchis, Pilar; Tamayo, María I.; Nicolau, Joana; Grases, Félix; Espino, Ana; Estremera, Ana; Rigo, Elena; Amengual, Guillermo J.; Rodríguez, Manuel; Ribes, José L.; Gomila, Isabel; et al. (Frontiers in Endocrinology, 2024)
Type 2 Diabetes Mellitus have a worldwide prevalence of 10.5% in the adult population (20-79 years) and by 2045, the prevalence is expected to keep rising to 1 in 8 adults living with diabetes. Mild cognitive impairment has a global prevalence of 19.7% in adults aged 50 years. Both conditions have shown a concerning increase in prevalence rates over the past 10 years, highlighting a growing public health challenge. Future forecasts indicate that the prevalence of dementia (no estimations done for individuals with mild cognitive impairment) is expected to nearly triple by 2050. Type 2 diabetes mellitus is a risk factor for the development of cognitive impairment, and such impairment increase the likelihood of poor glycemic/metabolic control. High phytate intake has been shown to be a protective factor against the development of cognitive impairment in observational studies. Diary phytate intake might reduce the micro and macrovascular complications of patients with type 2 diabetes mellitus through different mechanisms.We describe the protocol of the first trial (the PHYND trial) that evaluate the effect of daily phytate supplementation over 56 weeks with a two-arm double-blind placebo-controlled study on the progression of mild cognitive impairment, cerebral iron deposition, and retinal involvement in patients with type 2 diabetes mellitus. Our hypothesis proposes that phytate, by inhibiting advanced glycation end product formation and chelating transition metals, will improve cognitive function and attenuate the progression from Mild Cognitive Impairment to dementia in individuals with Type 2 Diabetes Mellitus and Mild Cognitive Impairment. Additionally, we predict that phytate will reduce iron accumulation in the central nervous system, mitigate neurodegenerative changes in both the central nervous system and retina, and induce alterations in biochemical markers associated with neurodegeneration.